What do we know about non-clinical interventions for preventable and treatable childhood diseases in developing countries? - Maureen Seguin; Miguel Ni\~no-Zarazúa (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
Preventable and treatable childhood diseases, notably acute respiratory infections and diarrhoeal diseases are the first and second leading causes of death and morbidity among young children in developing countries. The fact that a large proportion of child deaths are caused by these diseases is symptomatic of dysfunctional policy strategies and health systems in the developing world. Though clinical interventions against such diseases have been thoroughly studied, non-clinical interventions have received much less attention. This paper contributes to the existing literature on child wellbeing in two important respects: first, it presents a theory of change-based typology that emerges from a systematic review conducted on non-clinical interventions against preventable and treatable childhood diseases. Second, it pays particular attention to policies that have been tested in a developing country context, and which focus on children as the primary target population. Overall, we find that improved water supply and quality, sanitation and hygiene, as well as the provision of medical equipment that detect symptoms of childhood diseases, along with training and education for medical workers, are effective policy instruments to tackle diarrhoeal diseases and acute respiratory infections in developing countries.
Keywords: I15; I18; O15; O57; 330; health policy; respiratory infections; diarrhoeal diseases; children; developing countries; systematic review